Proposal and performance analysis of solar cogeneration system coupled with absorption heat pump. (August 2019) - Li, Xing; Wang, Zhifeng; Yang, Ming; Bai, Yakai; Yuan, Guofeng
Highlights: A new kind of solar cogeneration system coupled with absorption heat pump has been proposed. Mathematical models for energy and exergy analysis of the proposed system have been developed. Thermal performance of the proposed system with several design parameters has been evaluated. Unit heating cost with investment, operation parameters and power price has been investigated. Abstract: In this paper, a new kind of solar cogeneration system coupled with absorption heat pump (AHP) to recover condensate waste heat from exhaust of steam turbine in solar thermal power (STP) tower plant is proposed. Depending on mathematical models of the proposed system, several design parameters including direct normal irradiance (DNI), heat recovery ratio and improved power cycle are tested to evaluate their effects on the thermodynamic performance. Thermoeconomic investigations are also studied based on the existing AHP system installed in the pilot STP tower plant in Beijing. The results show that thermodynamic performance of the proposed system is improved due to energy and exergy contributions from steam storage tank (SST) and AHP. With the increase of DNI, the energy efficiency decreases accompanying with the increasing of exergy efficiency. As the condensate waste heat is completely recovered by AHP, the energy efficiency can reach up to 80.50%. Integrating with the improved regenerative cycle, the energy and exergy efficiencies can be increased from 16.90% to 17.17% and from 15.76% to 16.05%, respectively. Under the present base case, the unit heating cost decreases from 8.1 ¢/kWh to 2.8 ¢/kWh with the increase of operation time from 228 h to 2880 h.